Analisis Efisiensi Usahatani Lada di Desa Lalonggapu Kecamatan Landono Kabupaten Konawe Selatan - Surianti, Surianti; Rianse, Usman; Abdullah, Weka Gusmiarty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This research were aimed to (1) know the production of pepper production in Lalonggapu Village, Landono Sub-district of South Konawe Regency, (2) know the factors that influence the productivity of pepper farming in Lalonggapu Village, Landono Sub-district of South Konawe, (3) analyze level technical efficiency the use of production factors on pepper farming in Lalonggapu Village, Landono Sub-district, South Konawe Regency. The population in this study is all pepper farmers in Lalonggapu Village, LandonoSub-district, of South Konawe District. The sample in this study were 44 respondents who were determined by census method. The analysis method used is descriptive analysis, regression analysis with Cobb-Douglass production function equation and Data Envelopment Analysis (DEA). The results of this study indicate that the average of pepper production from 44 respondents in Lalonggapu Village, LandonoSub-district of South Konawe District is 509 kg/ha with the highest yield of 1100 kg/ha and the lowest production yield is 150 kg/ha. Production factors that affect productivity of pepper farming in LalonggapuVillage, LandonoSub-district of South Konawe District are land area, fertilizer and labor, while the production factors that do not have an effect on productivity of pepper farming inÂ  LalonggapuVillage, LandonoSub-district of South Konawe Districtare seed, pesticide and pepper species. Measurement of technical efficiency shows that pepper farming in Lalonggapu Village, Landono Sub-district of South Konawe District has not been able to achieve the overall efficiency level of technical efficiency. This indicated that there are still opportunities for pepper farmers to increase their production by optimizing their production factors